WHY AND HOW SUPRANATIONAL INSTITUTIONS BECAME CENTRAL STAKEHOLDERS IN THE EUROZONE DEBT CRISIS 2008–2012? - Veebel, Viljar; Markus, Raul (Baltic Journal of Political Science, 2013)
The financial crisis in the Eurozone is combining several new interdisciplinary debates. Has the financial crisis been caused by the decisions of the political actors or rather by complicated economic dilemmas? In what way have different social stakeholders acted during the years of the crisis and which of the groups have had the biggest influence in different stages of the crisis? Why and how national political elites have lost their dominant position in the crisis management, which have been the cornerstones of this power transition process and what role have the supranational institutions such as the European Commission and the European Central Bank played during the crisis? Accordingly, the main goal of the article is to define the crucial events and stakeholders in the Eurozone crisis solution process by using empirical process tracing and narrative analysis as the research methods. It will also inquire into how and why national political elites and citizens delegated their democratic competences and powers to non-electable institutions during the Eurozone crisis.